Increasing Junior High School Students' Career Understanding Through CapCut Media-Assisted Orientation Services - Dwi Lestari, Putri Indah; Hidayati, Novi Wahyu; Hastiani, Hastiani (Transpublika Publisher, 2024)
This research aims to improve understanding of advanced study planning through information services using the CapCut application for class IX C students at 22 Junior High School Pontianak. The method used is class action with two cycles. The research results demonstrate that students' talents and interests increased from 41% to 55% after the first action cycle and to 81% after the second cycle. Understanding secondary school improved from 42% in the poor category to 52% in the sufficient category after the first cycle of action. Following the second cycle, it further increased to 86% in the good category. The distinguishing aspect of secondary schools before the action was obtained was a percentage of 43% in the sufficient category, after being given action in cycle I it increased by 11% but was still in the sufficient category and after the implementation of cycle II it increased further by 34% to 88% in the good category. The aspect of making decisions and choosing a secondary school before the action was given, the percentage was 45% in the sufficient category, after being given the action in cycle I it increased by 10% but was still in the sufficient category and after the implementation of cycle II it increased by 34% to 89% in the good category. The use of the CapCut application in class IX C can enhance students' comprehension of planning for future studies by offering information services